Short forms of Prudhoe Cognitive Function Test in adults and aging people with intellectual disabilities: Italian validation study. - De Vreese, L. P.; Gomiero, T.; De Bastiani, E.; Marangoni, A.; Weger, E.; Mantesso, U. (Journal of Intellectual Disability Research, 2021)
Background: We aimed to validate the Italian version of the two parallel short forms of the Prudhoe Cognitive Function Test (s‐PCFT‐I) in adults and seniors with intellectual disabilities (ID) of any aetiology and level of severity. Methods: Our validation is a multicentre study attended by 211 subjects with ID, 125 male and 86 female, aged 40 years and above for people with Down syndrome and aged 50 years for people with other forms of disabilities. Results: The s‐PCFT‐I shows a wide range of scores in the absence of floor effects with minimal ceiling effects. A Cronbach's α coefficient of 0.85 and a mean inter‐item correlation of 0.21 indicate high internal consistency. The tool demonstrates good agreement between testers and near excellent temporal stability with intraclass correlation coefficients respectively of 0.85 and 0.90. s‐PCFT‐I total scores do not differ by sex or age, while statistically significant differences are observed between people with different levels of severity of ID. Moderate to good and highly significant correlations (−0.40 to −0.66) among the s‐PCFT‐I total scores and subscores and the Sum of Cognitive Score of the informant‐based Dementia Questionnaire for Persons with Intellectual Disabilities suggest an acceptable level of concurrent criterion validity. Cognitive decliners according to Prasher's Dementia Questionnaire for Persons with Intellectual Disabilities cut‐off scores perform significantly lower on s‐PCFT‐I than non‐decliners. Conclusions: The s‐PCFT‐I has good psychometric properties and user friendliness and may therefore be a valuable addition to the current informant‐rated tools for screening and assessment of cognition in aging people with ID.